PRIORITAS PROGRAM TERMINAL KAPAL PESIAR TANAH AMPO: SUATU PENERAPAN BENEFIT-COST ANALYSIS (BCA) UNTUK PENILAIAN PROYEK - Arnatha, Made; Budiartha R.M, Nyoman (Jurnal Ilmiah Teknik Sipil, 2012)
Benefit Cost Analysis (BCA) is the standard method used to aid agencies in project selection and prioritization, by measuring the efficiency costs from the perspective of the benefits for society that identifies optimum ratio of cost-benefit, usually by comparing the income of project beneficiaries. BCA is a computational tool to determine whether an investment will generate benefits that will exceed its costs. In the port industry, it is usually fragmented, BCA model raises the cost or benefit allocation problem that causes a variety of conceptual questions concerning the actual of cost or benefit in development and investment program. This study focuses on literature review of Benefit Cost Analysis (BCA) including port development feasibility study report on tourism in Tanah Ampo by the transport department of the Karangasem Regency Government in collaboration with the Research Institute (Research Center) University of Udayana and tourism port master plan study (RIP) in the Land ampo-Bali by the Directorate General of Sea Transportation in collaboration with the Research Institute (Research Center), University of Udayana, including: (a) a description of the maritime industry characteristics affecting the program plan, (b) requirements for program implementation, (c) methodology developed to evaluate projects, (d) review and evaluation of improvement.
Keywords: Benefit-Cost Analysis (BCA), inconsistent, Tanah Ampo Tourism Port